Properties of the cellular tissue of the city - Bolshakov, Andrey (project baikal, 2025)
The article uses the metaphors ‘cell’ and ‘tissue’ and analyses the configurations of motion networks for modelling the city. Such modelling is undertaken in order to identify the areas of harmonisation of the city and resolve its basic conflicts through ordering the properties of the cellular fabric. The article identifies the cell generation modes, the ways of binding cells into an entire tissue, interrelation of complex‑ ity and spatial entropy of the tissue. The article also reveals the properties of the tissue that contribute to the formation of landscape and historical framework of the city, as well as the formation of the coordinated transport, cycling and pedestrian flows. Cellular-network modelling of the urban fabric allows us to explain and see the ways of resolving the basic contradictions of the urban fabric.